Bacteriological and antibiotic sensitivity patterns of bacterial Isolates from creams and lotions hawked in Sagamu, Ogun State (2010)
Fifteen cosmetic products, consisting of 10 creams and 5 lotions were randomly purchased from a local market in sagamu and their microbial qualities studied in addition to the antibiotic sensitivity patterns of different isolates obtained from the selected creams and lotions. While only one of the creams was devoid of any microorganism including fungi, organisms isolated from others include Staphylococcus aureus 38%; Klebsiella, 28%; Pseudomonas aeruginosa, 21%; Bacillus spp, 7% and Penicillium, 28%. Antibiotic sensitivity study reveals that these isolates displayed different sensitivity patterns to the antibiotics used but cotrimoxazole, tetracycline and nalidixic acid will be of assistance in case of infection from these cosmetic products. However, majority of the creams and lotions evaluated did not meet the official monograph’s requirements and as such may be a potential health hazard to unsuspecting consumers moreso that all the isolates display some degree of resistance to various antibiotics used.